2020
DOI: 10.22492/ijl.9.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles, Promotion Opportunities, and Salary as Correlates of Turnover Intentions among Librarians in Nigerian University Libraries

Abstract: The study investigated leadership styles, promotion opportunities, and salary as correlates of turnover intention among librarians in Nigerian academic libraries. It applied the correlational survey design, and data was gathered with a questionnaire. The entire 115 librarians in three (3) universities in South-South, Nigeria formed the population of this study. The data was analyzed with mean and Pearson Moment Correlation (2-tailed). The findings show that the turnover intention of the librarians was high; le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The results found that organisational identification triggers employee intention to leave. According to Aiyebelehin et al (2020), positive employee identification reduces conflict and turnover intention. Therefore, organisational identification perceives as a critical necessity for employee job satisfaction and lower staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The results found that organisational identification triggers employee intention to leave. According to Aiyebelehin et al (2020), positive employee identification reduces conflict and turnover intention. Therefore, organisational identification perceives as a critical necessity for employee job satisfaction and lower staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows that promotional prospects have a negative and an inverse relationship with turnover intention (Ekabu et al, 2018). The finding shows that promotion opportunities positively correlate with turnover intention (Aiyebelehin et al, 2020). Based on the above review, the following is proposed:…”
Section: Promotions and Turnover Intentionsmentioning
confidence: 99%
“…This highlights the importance of identifying a comprehensive set of motivational strategies that align with employees' needs and aspirations, fostering a work environment conducive to high performance. Moreover, the limitations of relying solely on monetary incentives have been recognized within the banking sector, as excessive personnel turnover persists despite above-average compensation (Aiyebelehin et al, 2020). This implies the existence of other non-financial motivators that can effectively enhance employee performance.…”
Section: Introductionmentioning
confidence: 99%